Pengembanggan Model Pembelajaran Blended Learning Berbasis Edmodo dalam Membentuk Kemandirian Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas Xi Ips Sman 1 Selong Tahun Pelajaran 2017/2018 - Fahrurrozi, Muh; Majid, Muhip Abdul (Universitas Hamzanwadi, 2017)
Based on the observations of learning at SMAN 1 Selong indicate be present constraint on Economic Learning at class XI IPS of SMAN 1 Selong that is said by the subject’s teacher, amongs: less of innovation learning model applications that obtains contructions the students’ idea and ability, and leass complete of sstudy learning material so, there are some material left behind. One of efort to outcome the costraint are development and implementations of blended learning model base Edmodo and Economic subject with combinations the class surface learning and online. This research has a goal to formulate of planning, implementations, and verify learning effectiveness with blended learning model on Economic subject at class XI IPS of SMAN 1 Selong.The method that is used in this research are Research and Devlopment ADDIE model. Now the population of the risearch is all of the students of class XI IPS of SMAN 1 Selong. Wihile the reseach sample are the students of celass XI IPS and XI IPS 2 that is choozen by cluster sampling technique. The data collecting method are documentations, observations, test and quiz.The research result indicate that (1) the learning planinng and practical module with blended learning model base Edmodo is suitable used as orientations learning applications in the class, (2) learning implications, presentations, analysis and evaluations, organizations, investigations, presentations, analysis, and evaluations; (3) studying with blended learning evidents effective is refer to from aspects (a) Economic study result that use blended learning model base Edmodo > 75 and there is a difference result of study that significant between the group that use blended learning model base Edmodo; (b) the process in invropling self supporting and students’ study motivation is better. From the research result is suggested needed the development blended learning model base Edmodo as supplement close. Surface learning o Economic subject and other subject. Keywords: Development, Learning, Blended Learning Model, Edmodo, Economic Subject